1975
DOI: 10.1039/an9750000249
|View full text |Cite
|
Sign up to set email alerts
|

Fungicide residues. Part IV. Determination of residues of carboxin in grain by gas chromatography

Abstract: A simple method for determining residues of carboxin in grain is presented. The carboxin is extracted from the sample with acetone in a Soxhlet extraction apparatus and, after concentration of the extract, is determined by gasliquid chromatography using a nitrogen-selective detector. The presence of carboxin is confirmed by the use of a sulphur flame-photometric detector.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Chin et al (1970) studied the metabolism of carboxin by barley and wheat plants and developed a method for its direct determination by using gas chromatography with a microcoulometric sulfur detector. Farrow et al (1975) reported on the nitrogen-selective detector gas chromatographic determination of carboxin, after it had been extracted from the grain sample with acetone in a Soxhlet apparatus and concentrated. In this last procedure the limit of detection was at best 0.025 ppm, but the recovery was only checked to 0.5 ppm.…”
Section: Determination Of Residues Of Vitavax and Plantvax In Grainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chin et al (1970) studied the metabolism of carboxin by barley and wheat plants and developed a method for its direct determination by using gas chromatography with a microcoulometric sulfur detector. Farrow et al (1975) reported on the nitrogen-selective detector gas chromatographic determination of carboxin, after it had been extracted from the grain sample with acetone in a Soxhlet apparatus and concentrated. In this last procedure the limit of detection was at best 0.025 ppm, but the recovery was only checked to 0.5 ppm.…”
Section: Determination Of Residues Of Vitavax and Plantvax In Grainsmentioning
confidence: 99%
“…The grain extracts were not purified and this resulted in an increase in the standing current, a loss of resolution and a shorter column life. Therefore, Farrow et al (1975) recommended that 20-g samples of the grain be employed for the analysis and that the first 10 cm of column packing be replaced after 50 sample injections. When this method was applied to oxycarboxin, it failed, because the response varied by ±25%.…”
Section: Determination Of Residues Of Vitavax and Plantvax In Grainsmentioning
confidence: 99%